Decomposition-adsorption-deposition: An effective and novel technique for synthesis of hexagonal boron nitride microsheets. (December 2018) - Ahmad, Pervaiz; Khandaker, Mayeen Uddin; Muhammad, Nawshad; Ahmad, Iftikhar; Rauf Khan, M. Abdul; Khan, Ayaz Arif; Khan, Ghulamullah; Khan, Amir Sada; Ullah, Zahoor; Rehman, Fida; Ahmed, Syed Muzamil; Ali, Hazrat; et al.
Abstract: Magnesium diboride as a precursor with dual role of Nitrogen introduces a simple "decomposition-adsorption-deposition (DAD)" technique for the synthesis of Hexagonal Boron nitride microsheets (BNMSs) on silicon (Si) substrate at 1100 °C. The synthesized BNMSs has the apparent morphology like the white dispersed feathers on a plate surface with diameter in the range of 3–15 µm and lengt greater than 30 µm. All the BNMSs has the characteristics of h -BN lattice with an interlayer spacing of 0.34 nm. Boron and Nitrogen elemental compositions and h -BN phase of the synthesized BNMSs are verified from its characterization by X-ray photoelectron spectroscopy (XPS), Fourier transformed infrared (FTIR) spectroscopy and Raman.